BRNS Sponsored National Symposium: Radiotracer Techniques: Improve Nutritional Status and Health of Animals and Plants - Indore, CDIP (Journal of Drug Delivery and Therapeutics, 2020)
BRNS Sponsored National Symposium on"Radiotracer Techniques: Improve Nutritional Status and Health of Animals and Plants" Organized By: Chameli Devi Institute of Pharmacy, IndoreSaturday, 1st February 2020